Полином как единица вокабуляра - Жукова, Л.К. (Культура народов Причерноморья, 2004)
English system of nominalization is rapidly being enriched by the nominative structures of N+N(+N+…Nn) type. The most appropriate term for them is polynom. The nature of polynoms is rather lexical than syntactic. Components of polynoms may have different semantic relations. Polynoms have hierarchial structure, the core of which is the binom. In the future polynoms may turn into acronyms, blendings or complex nouns.